2013
DOI: 10.1016/j.ab.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A capillary electrophoretic assay for acetyl coenzyme A carboxylase

Abstract: A simple off-column capillary electrophoretic (CE) assay for measuring acetyl coenzyme A carboxylase holoenzyme (holo-ACC) activity and inhibition was developed. The two reactions catalyzed by the holo-ACC components, biotin carboxylase (BC) and carboxyltransferase (CT), were simultaneous monitored in this assay. Acetyl coenzyme A (CoA), malonyl-CoA, adenosine triphosphate (ATP), and adenosine diphosphate (ADP) were separated by CE, and the depletion of ATP and acetyl-CoA as well as the production of ADP and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The first separation buffer used during the development of this assay contained 15.0 mM Tris-HCl and 30 mM SDS at pH 8.00. It has been reported that addition of SDS improves the separation of ATP and ADP [20; 21]. Under these conditions (above the SDS critical micelle concentration), the separation is a micellar enhanced capillary electrokinetic chromatography (MEKC) separation [22].…”
Section: Resultsmentioning
confidence: 99%
“…The first separation buffer used during the development of this assay contained 15.0 mM Tris-HCl and 30 mM SDS at pH 8.00. It has been reported that addition of SDS improves the separation of ATP and ADP [20; 21]. Under these conditions (above the SDS critical micelle concentration), the separation is a micellar enhanced capillary electrokinetic chromatography (MEKC) separation [22].…”
Section: Resultsmentioning
confidence: 99%
“…The ACC2 assay based on CE depends on the separation and quantification of the nucleotide substrates and products – ATP, ADP, acetyl‐CoA, and malonyl‐CoA. Previous CE assays for bacterial ACC and phosphofructokinase‐1 included methods for separation of nucleotides based on earlier published separations ; however, the development of the ACC2 assay inspired a re‐examination of those previous nucleotide separations.…”
Section: Resultsmentioning
confidence: 99%
“…The injected sample will contain the solution used for the enzyme‐catalyzed reaction, and its injection must not degrade the CE separation. Separation of these four molecules has been demonstrated for an assay of bacterial ACC , but optimum solution conditions for human ACC2 and bacterial ACC are significantly different . The separation was revisited, based on the reaction requirements of human ACC2 and our experience working with bacterial ACC and phosphofructokinase‐1 (PFK‐1), another Mg 2+ ‐dependent enzyme .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations